EURAD state-of-the-art report: thermo-hydro-mechanical behaviour at high temperature of host clay formations - Villar, María Victoria; Bésuelle, Pierre; Collin, Frédéric; Cuss, Robert; de Lesquen, Christophe; Dizier, Arnaud; El Tabbal, Ginger; Gens, Antonio; Graham, Caroline; Grgic, Dragan; Harrington, Jon; Imbert, Christophe; et al. (Frontiers in Nuclear Engineering, 2025)
Most safety cases for radioactive waste disposal concepts consider a temperature limit of 90°C in the clay host rock. Being able to tolerate higher temperature would have significant advantages. For this reason, part of the EURAD-HITEC project aimed at determining the influence of temperature above 90°C on clay host rock properties, trying to establish the possible extent of elevated temperature damage in the near and far field of clay host rock formations and the consequences of any such damage. Three clay formations considered to host radioactive waste repositories in Europe were the focus of the studies: the Boom Clay, the Callovo-Oxfordian claystone and the Opalinus Clay. A summary of the background knowledge about the thermo-hydro-mechanical behaviour of these clay host rocks is first presented. Then, the experimental and modelling activities carried out in the framework of the EURAD-HITEC project concerning these materials have been synthesised. The laboratory tests analysed the impact of temperature on the short- and long-term behaviour of the clay host rock and the self-sealing processes. Hydro-mechanical couplings between peak pore water pressure, temperature, permeability and confining stress were identified. The results confirmed that the claystone keeps its good mechanical and retention properties even when heated up to 100°C. Provided that the clay content of the samples is high enough, self-sealing was an efficient mechanism whatever the experimental conditions, although temperature may have a delaying effect. Poro-elastic models were used to model generic cases of a high-level waste repository, and consistent results were obtained by the different codes and teams, which shows the robustness of the modelling approach used to design the repositories. Two heating tests, performed in the HADES (Belgium) and MHM (France) underground research laboratories, were selected as benchmarks for the modelling activities. The evolutions of temperature and pore pressure were well modelled in the far field with a poro-elastic approach, but more advanced models are needed to take into account the processes occurring around the tunnels (e.g., modification of hydraulic properties within the EDZ, creep). The modelling of laboratory experiments showed the importance of a good understanding of the tests setup and of the boundary conditions.